A new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Quiriri, northeastern Santa Catarina state, southern Brazil, with a review of the diagnosis among species of the B. pernix group and proposed conservation measures - Marcos R. Bornschein; Marcio R. Pie; Júnior Nadaline; André E. Confetti; David C. Blackburn; Edward L. Stanley; Renata de Britto Mari; Gabriel Silveira Alves; Giovanna Sandretti-Silva; Felipe Farias de Andrade Lima; Luiz F. Ribeiro (PLoS ONE, 2025)
Brachycephalus are miniaturized diurnal frogs inhabiting the leaf litter of the Brazilian Atlantic Forest, mainly in montane areas. The genus includes 42 currently recognized species, 35 of which being described since 2000. This study describes a new species of Brachycephalus from the B. pernix species group discovered at Serra do Quiriri, Santa Catarina, Brazil. Morphological and acoustic comparisons were made with other species in the species group, and high-resolution computed tomography was used for osteological examination. The phylogenetic position was based on partitioned Bayesian analysis of mitochondrial (16S rRNA) and nuclear DNA sequences (β–fibrinogen, ribosomal Protein L3, and tyrosinase exon 1). We collected 32 individuals and recorded 13 calls of the new species. It is distinguished by 18 characters including snout–vent length 8.9–11.3 mm for males and 11.7–13.4 mm for females, general bright orange coloration of the body with small green and brown irregular points, and advertisement call including note groups (two notes per group, with 1–4 pulses per note). Phylogenetic data indicate that the new species is closely related to B. auroguttatus and B. quiririensis , which also occur at Serra do Quiriri. A review of diagnoses among species of the B. pernix group is provided. We propose classifying the new species as Least Concern. Serra do Quiriri experienced semi-arid periods in the Quaternary, with forests likely occurring at lower altitudes. As the climate became wetter, these forests expanded upward as cloud forests, forming patches amidst grasslands, leading to speciation by allopatry (microrefugia) of B. quiririensis , B. auroguttatus , and the new species. This process continues, with recent observations of Brachycephalus colonizing newly formed cloud forests at high altitudes. We propose the creation of the Refúgio de Vida Silvestre (RVS) Serra do Quiriri to protect this and other endemic species, without requiring government acquisition of private land.